Tingkat Pemahaman Generasi Z terhadap Wakaf Uang di Kota Pekanbaru - Haniah Lubis (el-Jizya : Jurnal Ekonomi Islam, 2023)
This study aims to determine the level of understanding of Generation Z on cash waqf and find ways to increase Generation Z's understanding of cash waqf in Pekanbaru City. The approach taken is a quantitative descriptive approach. The population in this study is Generation Z with the status of students, namely the Islamic Economics Study program of UIN Sultan Syarif Kasim Riau. The total population is 1,107 people. A sample of 96 people was taken, which was obtained through the slovin formula. The results of the study obtained an average research score of 350, located in the area of ​​​​agree close to doubt. So it is stated that the level of understanding of Generation Z on cash waqf is classified as quite good. Efforts taken in increasing the understanding of Generation Z towards cash waqf in Pekanbaru City can be done in various ways including increasing literacy of cash waqf in Generation Z through educational activities, socialization activities through media that can be accessed easily, utilizing QRIS as a means of cash waqf, and attracting interest in waqf using the services of influencers.